Engineering human trust in mobile system collaborations. - Capra, Licia (Software engineering notes.)
Rapid advances in wireless networking technologies have enabled mobile devices to be connected anywhere and anytime. While roaming, applications on these devices dynamically discover hosts and services with whom interactions can be started. However, the fear of exposure to risky transactions with potentially unknown entities may seriously hinder collaboration. To minimise this risk, an engineering approach to the development of trust-based collaborations is necessary. This paper introduces hTrust, a human trust management model and framework that facilitates the construction of trust-aware mobile systems and applications. In particular, hTrust supports: reasoning about trust (trust formation), dissemination of trust information in the network (trust dissemination), and derivation of new trust relationships from previously formed ones (trust evolution). The framework views each mobile host as a self-contained unit, carrying along a portfolio of credentials that are used to prove its trustworthiness to other hosts in an ad-hoc mobile environment. Customising functions are defined to capture the natural disposition to trust of the user of the device inside our trust management framework.